Análisis sero-inmunológico de diferentes niveles de especiación en Bufo del grupo spinulosus - Cei, José Miguel Alfredo María (1971)
Speciation of the Bufo spinulosus complex is strikingly demonstrated on its wide area of distribution by means of the antigenic properties of the serum proteins. Serological relationships between different populational groups from Peru, Chile and were studied. Precipitin tests were measured by means of the Libby’s Photroner. Percentages above 90 % concern with populational and geographical variation; but under 90 % a real inter-specific relationship can be claimed. The following specific units were stressed: limensis Werner, flavilineatiis (Vellard), trifolium Tschudi, aiacamensis (Cei), chilensis Dum. Bib., spinulosus Wiegmann, rubropunctatus Guiclienot. The remarkable serological isolation of the so called “spinulosus” form from Pampa de Achala, Córdoba, is especially emphasized.